PENGARUH DEBT TO EQUITY RATIO DAN NET PROFIT MARGIN TERHADAP NILAI PERUSAHAAN DI BURSA EFEK INDONESIA - Simanjuntak, Elvis; Ningsih, Desrini (EDUTECH CONSULTANT, 2020)
Each year the ratio of the firm value measurement, debt to equity ratio and net profit margin to manufacturing companies in the pharmaceutical sub sectors has always fluctuated. It can be seen from the financial statements listed on the Indonesia Stock Exchange. The high firm value will attract investors to grow stocks so that they can increase the company's finances. This research aims to determine the influence of debt to equity ratio and net profit margin against the value of companies in the stock exchange. The number of population in this assessment was 9 companies in the pharmaceutical sub-sector listed on the stock Exchange in 2014-2018. The sampling techniques used in this study are using purposive sampling methods so there are 7 companies that meet the criteria. This research uses secondary data. The Data in this study was obtained from the official website of the Indonesia Stock Exchange and IDX office of Riau Islands. The study uses SPSS program version 22 in data processing. T test results are partially, debt to equity ratio and net profit margin significantly affect the firm value. F test results are simultaneously debt to equity ratio and net profit margin significantly affect the firm value.